Commuting Efficiency Gains: Assessing Different Transport Policies with New Indicators. Issue 10 (26th November 2019) - Zhou, Jiangping; Murphy, Enda; Long, Ying
Abstract: This paper outlines new indicators for evaluating the probable impacts of introducing different land use/transport policies on the commuting efficiency of a city. It uses Beijing as a case study to describe how smartcard data can be used to derive a large number ( n = 216, 884, 9% of the population) of bus commuters' workplace and residential locations. Using existing excess commuting indicators and new commuting efficiency gain indicators established to assess policy options, it exemplifies how to assess impacts of different policies on bus commuting efficiency gains. The case study indicates policies that directly target bus commuters (such as BRT) bring greater commuting efficiency gains when compared to other policies such as car usage restrictions and stringent travel demand management measures in the downtown area.